Robotic-assisted surgery in the pediatric surgeons' world: Current situation and future prospectives - Hong Mei; Shaotao Tang (Frontiers Media S.A., 2023)
Robotic-assisted surgery has been fully embraced by surgeons for the adult population; however, its acceptance is too slow in the world of pediatric surgeons. It is largely due to the technical limitations and the inherent high cost associated with it. In the past two decades, indeed, there has been considerable advancement in pediatric robotic surgery. A large number of surgical procedures were performed on children with the assistance of robots, even with comparative success rates to standard laparoscopy. As a newly developing field, it still has many challenges and obstacles. This work is centered on the current status and progression of pediatric robotic surgery as well as the future perspectives in the field of pediatric surgery.